Focused - Gerber, Alyson (Scholastic Press, 2019)
After Clea fails yet another test, her parents take her to the doctors and she is diagnosed with ADHD. Her attention is all over the place, and that has to change, life can't continue the way it has been--Clea has to fight through to find a way to focus and get her life back on track.